Case report: Iliac vein rupture during endovascular stenting in radiation-induced iliac venous stenosis - Xiang, Qilin; Tian, Jinbo; Zhu, Xiaoling; He, Chunshui; Huang, Shan (Frontiers in Oncology, 2023)
Only a few case reports in the medical literature describe radiation-induced iliac vein stenosis and endovascular therapy. We present a case of left external iliac vein stenosis resulting from radiotherapy for cervical cancer in which the iliac vein ruptured during the standard iliac vein stenting procedure. The emergency condition was resolved with the implantation of a covered stent and resuscitation with crystalloid and blood transfusion. The patient recovered without additional complications and was discharged eight days after endovascular therapy. At the six-month follow-up, the left lower limb edema had resolved completely, and the deep vein remained patent. This case might raise concerns regarding the potential risk of treating radiation-induced iliac venous stenosis, which may differ from that of a patient without a history of radiation therapy. Iliac vein rupture, iliac vein stenting, radiation-induced venous stenosis, case report